The end of full employment? On economic development in industrialized countries - Eileen Appelbaum; Ronald Schettkat (Intereconomics, 1994)
In view of high and rising jobless rates in the industrialized countries the solution of the unemployment problem becomes a cardinal question for politicians and economists. What factors have determined the unemployment trend since the 1960s and what conclusions can be drawn for employment policy?
Keywords: 330; Unemployment